Navvāb Faṣīḥulmulk Dāg̲ẖ Dihlavī kī savāniḥ ḥayāt aur kalām par mabsūt̤ tabṣirah - Nūrī, Nūrullāh Muḥammad (SAMP early 20th-century Indian books project, 1936)
Life and works of Dāg̲ẖ Dihlavī, 1831-1905, Urdu poet.